Bitter pills: the global war on counterfeit drugs - Zaman, Muhammad H. (Oxford University Press, 2018)
Cities in crisis -- The life of a pill -- An age-old problem -- Of mice and cats -- Unaware, unable or unwilling? -- Crime and punishment -- Trust and mistrust -- The disconnected citizens -- The technological fix? -- The ivory trade